Multidisciplinary Bear Deterrent System - Cindea, Dumitru Ioan; Sasaran, Andrei Mihnea; Stefan, Iulia Adina (International Conference on System Theory, Control and Computing, 2025)
Human-bear interactions have become increasingly frequent in mountainous areas due to food scarcity in natural habitats. To prevent unpleasant encounters, this paper presents an autonomous multidisciplinary bear deterrent system (MBDS) developed for mountain highway areas. The system combines artificial intelligence detection techniques, remote observation, and remote access and positioning of cameras followed by distributed acoustic dispersion, an important part of this innovative system proposed due to its multiple integrated technologies. The problem of human-bear interactions in this tourist area requires a noninvasive approach that protects both people and wildlife. Using a central visual detection mechanism, the system identifies bear presence, and coordinately activates animal redirection without causing stress or aggressiveness.